Effect of foliar spraying with yeast extract and boron on growth and yield of potato Solanum tuberosum cv.spunta - شيخ سليمان نصر; عثمان جنان; حمد ديانا (Latakia University Journal -Biological Sciences Series, 2022)
The study was conducted in the village of Berna in Lattakia governorate during the spring season of 2018/2019 ,in order to study the effect of foliar spraying with yeast extract and boron on growth and yield of potato solanum tuberosum cv. Spunta.The experiment included nine treatments (treatment of plants with yeast at two concentrations with or without spraying with boron at two concentrations on the indicators of vegetative growth and productivity,according to the desighn of complete random sectors with three replications per treatment and the rate of ten plants per repeatter The results showed the positive effect of foliar spraying with yeast extract and boron in increasing the leaf area of the plant and its guide,as it reached highest area of the leaf surface and its guide in treatment T9(spraying plants with yeast extract at aconcentration of 6g.l-1 and with boric acid at aconcentration of 600 ppm ),where this treatment significantly outperformed the rest of the studied treatments 13455 cm2.plant-1 it also gave the highest values for stem length 80 cm as well as the highest Productivity of unit area 5.17 kg.meter-1and the highest values for the number of tubers per plant 10.80tuberper plant while excelled treatement T5to the rest of transactions in average weight tuber133.25 gram .